Graphene heat-conducting film and preparation method thereof

CN119430938BActive Publication Date: 2026-10-20SHENZHEN QIANHAI GRAPHENE IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411621213.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2026-10-20
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

[0004]本发明要解决的技术问题为:现有高分子薄膜石墨化法中,温度高能耗大,石墨化晶态结构不稳定,存在无定型态缺陷的问题

Benefits of technology

本发明提供了一种石墨烯导热膜的制备方法,通过石墨烯负载镍诱导并催化聚酰亚胺薄膜的石墨化,从而降低石墨化温度,传统方法的石墨化温度为2500℃~3000℃,本发明的石墨化温度最低可降低至1500℃,极大的减少了生产能耗;提高了石墨化晶态结构,减少无定型态缺陷。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application relates to the technical field of electronic devices, in particular to a graphene heat-conducting film and a preparation method thereof. In view of the problems of high temperature, high energy consumption, unstable graphitization crystal structure and existing amorphous defects in the graphitization method of the existing polymer film, the application provides a preparation method of the graphene heat-conducting film, the method comprises the following steps: reacting water-soluble nickel salt and graphene to obtain nickel-loaded graphene powder; generating a viscous polyamide acid solution in the reaction; obtaining a polyimide composite film after imidization; and obtaining the graphene heat-conducting film after graphitization. The application induces and catalyzes the graphitization of the polyimide film by loading nickel on the graphene, so that the graphitization temperature is reduced, the energy consumption is reduced, the graphitization crystal structure is improved, and the amorphous defects are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electronic device technology, specifically to a graphene thermal conductive film and its preparation method. Background Technology

[0002] With the rapid development of technology, electronic products are becoming increasingly integrated, leading to a surge in demand for microelectronic components. This has resulted in problems such as high heat generation and uneven heat dissipation, with excessive heat severely impacting the normal operation of electronic devices and system stability. Traditional thermal conductive materials are primarily metals such as copper and aluminum foil. While these metal thermal conductive materials are relatively mature, they suffer from drawbacks such as poor thermal conductivity, heavy weight, and poor corrosion resistance, making it difficult to meet the current demands of electronic devices for high thermal conductivity, lightweight, and high weather resistance. Compared to traditional metal materials, graphene not only possesses higher thermal conductivity but also exhibits advantages such as light weight and strong corrosion resistance. Therefore, graphene shows greater potential in meeting the thermal conductive material requirements of electronic devices. Among the various forms of graphene, it can effectively meet the application scenarios of traditional metal thermal conductive materials such as aluminum and copper foil, thus attracting significant attention and in-depth research as a next-generation high-performance thermal conductive material.

[0003] Currently, there are four main methods for preparing graphene thermal conductive films: expanded graphite calendering, chemical vapor deposition, graphene oxide reduction, and polymer film graphitization. Compared to the low thermal conductivity of expanded graphite calendering, the demanding conditions of chemical vapor deposition, and the severe pollution of graphene oxide reduction, graphene thermal conductive films prepared by polymer film graphitization typically exhibit good flexibility and thermal conductivity, and the process is simple. However, this method also has many drawbacks, such as high energy consumption during high-temperature graphitization and the tendency to generate a large number of incompletely graphitized amorphous states, which seriously affect the thermal and electrical conductivity of the graphene thermal conductive film and its production efficiency. Therefore, how to reduce the graphitization temperature while improving the graphitized crystalline structure and reducing amorphous defects is a crucial problem that urgently needs to be solved for graphene thermal conductive films. Summary of the Invention

[0004] The technical problem to be solved by this invention is that in the existing polymer thin film graphitization method, the temperature is high, the energy consumption is large, the graphitized crystalline structure is unstable, and there are amorphous defects.

[0005] The technical solution of this invention to solve the above-mentioned technical problems is as follows: a method for preparing a graphene thermally conductive film is provided, comprising the following steps: a) Disperse water-soluble nickel salt in a solvent and sonicate to obtain solution A; disperse graphene and reducing agent in a solvent, adjust the pH to 11-13, and sonicate to obtain solution B; b. Transfer solutions A and B to a high-pressure reactor, add surfactant, and hydrothermally react at 40–120°C for 1–24 h. After cooling, centrifugation, washing, and drying, nickel-loaded graphene powder is obtained. c. Dissolve nickel-loaded graphene powder and diamine in N,N-dimethylacetamide (DMAC) and transfer to a high-pressure reactor. Use nitrogen as a protective gas, add dianhydride to the reactor, and react for 6-24 hours to obtain a viscous polyamic acid solution. d. The viscous polyamic acid solution is uniformly coated on a 2×2cm glass plate, and then imidized in a heating furnace at 100℃~300℃ for 1~6h to obtain a polyimide composite film. The film is placed in an isostatically pressed graphite block and sent to a high-temperature graphitization furnace. In the high-temperature graphitization furnace, it is first carbonized at 800℃~1200℃ for 1~6h, and then graphitized at 1500℃~3000℃ for 1~6h to obtain a graphene thermal conductive film.

[0006] In the above-mentioned method for preparing the graphene thermally conductive film, the water-soluble nickel salt in step a is at least one selected from nickel nitrate, nickel chloride, nickel bromide, nickel fluoride, nickel iodide, nickel sulfate, nickel hydroxide, nickel acetylacetonate, or nickel acetate tetrahydrate. Nickel chloride is preferred.

[0007] In the above-mentioned method for preparing the graphene thermally conductive film, the solvent in step a is at least one of water or ethanol. Water is preferred.

[0008] In the above-mentioned method for preparing the graphene thermally conductive film, the concentration of solution A in step a is 0.01–0.5 mol / L, preferably 0.02 mol / L.

[0009] In the above-mentioned method for preparing the graphene thermally conductive film, the reducing agent in step a is at least one of hydrazine hydrate, sodium borohydride, ascorbic acid, or ethylene glycol. Hydrazine hydrate is preferred.

[0010] In the above-mentioned method for preparing graphene thermal conductive film, the molar ratio of graphene to reducing agent in liquid B in step a is 0.5 to 16:1, preferably 5:1.

[0011] In the above-mentioned method for preparing graphene thermal conductive film, the volume ratio of liquid A to liquid B in step a is 1:1 to 5.

[0012] In the above-mentioned method for preparing graphene thermal conductive film, the pH adjustment in step a is performed using a 1 mol / L sodium hydroxide solution.

[0013] In the above-mentioned method for preparing the graphene thermally conductive film, the surfactant in step b is at least one of N-methylpyrrolidone, Triton, or melamine. N-methylpyrrolidone is preferred.

[0014] In the above-mentioned method for preparing the graphene thermally conductive film, the amount of surfactant added in step b is: the mass ratio of surfactant to graphene is 0.5 to 5:1, preferably 1:1.

[0015] In the above-mentioned method for preparing graphene thermal conductive film, the reaction temperature in step b is preferably 70°C, and the reaction time is preferably 7 hours.

[0016] In the above-mentioned method for preparing the graphene thermally conductive film, the cooling in step b is natural cooling. The washing involves washing three times each with deionized water and ethanol. The drying involves vacuum drying at a temperature of 50–100°C for 2–24 hours, preferably at 60°C for 12 hours.

[0017] In the above-mentioned method for preparing the graphene thermally conductive film, the diamine in step c is at least one of 4,4'-diaminodiphenyl ether, p-phenylenediamine, poly(p-phenylene terephthalamide), or 4,4'-(hexafluoroisopropylidene)phthalic anhydride. Preferably, it is 4,4'-diaminodiphenyl ether.

[0018] In the above-mentioned method for preparing the graphene thermally conductive film, the dianhydride in step c is at least one selected from pyromellitic dianhydride, 4,4'-biphenyl ether dianhydride, 1,2,4,5-benzenetetracarboxylic anhydride, or 1,4-bis(4-amino-2-trifluoromethylphenoxy)benzene. Pyromellitic dianhydride is preferred.

[0019] In the above-mentioned method for preparing the graphene thermally conductive film, the mass ratio of nickel-loaded graphene powder to diamine in step c is 1:1 to 10, preferably 1:4. The molar ratio of diamine to dianhydride is 1:1.

[0020] In the above-mentioned method for preparing graphene thermal conductive film, the reaction time in step c is 8 hours.

[0021] In the above-mentioned method for preparing the graphene thermally conductive film, the imidization temperature in step d is 200℃, and the time is 1 hour. The carbonization temperature is 800℃, and the carbonization time is 1 hour. The graphitization temperature is 1500℃, and the time is 1 hour.

[0022] The present invention also provides a graphene thermally conductive film directly prepared by the above method.

[0023] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention provides a method for preparing a graphene thermally conductive film. By inducing and catalyzing the graphitization of a polyimide film with nickel loaded on graphene, the graphitization temperature is reduced. The graphitization temperature of traditional methods is 2500℃~3000℃, while the graphitization temperature of this invention can be reduced to as low as 1500℃, which greatly reduces production energy consumption; it also improves the graphitized crystalline structure and reduces amorphous defects. Detailed Implementation

[0024] This invention primarily reduces the graphitization temperature and decreases the amorphous state by inducing and catalyzing the graphitization of polyimide films with nickel supported on graphene.

[0025] Nickel is a catalyst that reduces the energy required for graphitization through catalysis, enabling the graphitization process to be carried out at relatively low temperatures, thereby improving production efficiency and reducing energy consumption.

[0026] The orbital hybridization of nickel atoms results in less steric hindrance on the surface, which can effectively adsorb and stabilize carbon atoms, promoting the formation of a more ordered graphite structure. As the reaction proceeds, amorphous carbon is gradually transformed into graphite.

[0027] Therefore, the present invention reduces the graphitization temperature, reduces energy consumption, and also reduces defects in amorphous states.

[0028] The specific implementation of the present invention will be further explained and described below through examples, but this does not mean that the scope of protection of the present invention is limited to the scope described in the examples.

[0029] Example 1: Preparation of the nickel-catalyzed graphene thermally conductive film of the present invention.

[0030] Includes the following steps: (1) Disperse 1g of nickel chloride hexahydrate in 200mL of aqueous solution and sonicate to obtain solution A; (2) Disperse 8g of graphene and 17mL of hydrazine hydrate in 800mL of aqueous solution, adjust the pH value to 12 with 1mol / L sodium hydroxide solution, and sonicate to obtain solution B; (3) Transfer liquids A and B to a high-pressure reactor and add 8g of N-methylpyrrolidone. React hydrothermally at 70°C for 7 hours.

[0031] (4) Cool naturally to room temperature, centrifuge the sample, wash it three times with deionized water and ethanol, and dry it in a vacuum drying oven at 60℃ for 12 hours to obtain graphene-supported nickel nanoparticle powder.

[0032] (5) Dissolve graphene-supported nickel nanoparticle powder and 0.2 mol of 4,4'-diaminodiphenyl ether in 1 L of DMAC and transfer it to a high-pressure reactor, using nitrogen as a protective gas.

[0033] (6) Add 0.2 mol of pyromellitic dianhydride to the reaction vessel and react for 8 h to obtain a viscous polyamic acid solution.

[0034] (7) The polyamic acid solution was uniformly coated on a 2×2cm glass plate, and then imidized at 200℃ for 1h in a heating furnace to obtain a PI composite film.

[0035] (8) Place the PI film into an isostatic graphite block and send it into a high-temperature graphitization furnace.

[0036] (9) First carbonize at 800℃ for 1h in a high-temperature graphitization furnace, and then graphitize at 1500℃ for 1h to obtain a graphene thermal conductive film.

[0037] Example 2: Preparation of the nickel-catalyzed graphene thermally conductive film of the present invention.

[0038] Includes the following steps: (1) Disperse 4g of nickel chloride hexahydrate in 200mL of aqueous solution and sonicate to obtain solution A; (2) Disperse 8g of graphene and 0.8mL of hydrazine hydrate in 800mL of aqueous solution, adjust the pH value to 11 with 1mol / L sodium hydroxide solution, and sonicate to obtain solution B; (3) Transfer liquids A and B to a high-pressure reactor and add 8g of N-methylpyrrolidone. React hydrothermally at 90°C for 12 hours.

[0039] (4) Cool naturally to room temperature, centrifuge the sample, wash it three times with deionized water and ethanol, and dry it in a vacuum drying oven at 80℃ for 6 hours to obtain graphene-supported nickel nanoparticle powder.

[0040] (5) Dissolve graphene-supported nickel nanoparticle powder and 0.2 mol of 4,4'-diaminodiphenyl ether in 1 L of DMAC and transfer it to a high-pressure reactor, using nitrogen as a protective gas.

[0041] (6) Add 0.2 mol of pyromellitic dianhydride to the reaction vessel and react for 16 h to obtain a viscous polyamic acid solution.

[0042] (7) The polyamic acid solution was uniformly coated on a 2×2cm glass plate, and then imidized at 150℃ for 2h in a heating furnace to obtain a PI composite film.

[0043] (8) Place the PI film into an isostatic graphite block and send it into a high-temperature graphitization furnace.

[0044] (9) First carbonize at 1000℃ for 2 hours in a high-temperature graphitization furnace, then graphitize at 2400℃ for 2 hours to obtain a graphene thermal conductive film.

[0045] Example 3: Preparation of the nickel-catalyzed graphene thermally conductive film of the present invention.

[0046] Includes the following steps: (1) Disperse 0.5g of nickel chloride hexahydrate in 200mL of aqueous solution and sonicate to obtain solution A; (2) Disperse 8g of graphene and 0.8mL of hydrazine hydrate in 800mL of aqueous solution, adjust the pH value to 13 with 1mol / L sodium hydroxide solution, and sonicate to obtain solution B; (3) Transfer solutions A and B to a high-pressure reactor and add 8g of N-methylpyrrolidone. React hydrothermally at 50°C for 24 hours.

[0047] (4) Cool naturally to room temperature, centrifuge the sample, wash it three times with deionized water and ethanol, and dry it in a vacuum drying oven at 70℃ for 24 hours to obtain graphene-supported nickel nanoparticle powder.

[0048] (5) Dissolve graphene-supported nickel nanoparticle powder and 0.2 mol of 4,4'-diaminodiphenyl ether in 1 L of DMAC and transfer it to a high-pressure reactor, using nitrogen as a protective gas.

[0049] (6) Add 0.2 mol of pyromellitic dianhydride to the reaction vessel and react for 12 h to obtain a viscous polyamic acid solution.

[0050] (7) The polyamic acid solution was uniformly coated on a 2×2cm glass plate, and then imidized at 300℃ for 5h in a heating furnace to obtain a PI composite film.

[0051] (8) Place the PI film into an isostatic graphite block and send it into a high-temperature graphitization furnace.

[0052] (9) First carbonize at 900℃ for 1 hour in a high-temperature graphitization furnace, then graphitize at 2000℃ for 1 hour to obtain a graphene thermal conductive film.

[0053] Example 4: Preparation of the nickel-catalyzed graphene thermally conductive film of the present invention.

[0054] Includes the following steps: (1) Disperse 1g of nickel chloride hexahydrate in 200mL of aqueous solution and sonicate to obtain solution A; (2) Disperse 8g of graphene and 1.3g of sodium borohydride in 800mL of aqueous solution, adjust the pH to 12 with 1mol / L sodium hydroxide solution, and sonicate to obtain solution B; (3) Transfer liquids A and B to a high-pressure reactor and add 8g of N-methylpyrrolidone. React hydrothermally at 70°C for 8 hours.

[0055] (4) Cool naturally to room temperature, centrifuge the sample, wash it three times with deionized water and ethanol, and dry it in a vacuum drying oven at 70℃ for 12 hours to obtain graphene-supported nickel nanoparticle powder.

[0056] (5) Dissolve graphene-supported nickel nanoparticle powder and 0.2 mol of 4,4'-diaminodiphenyl ether in 1 L of DMAC and transfer it to a high-pressure reactor, using nitrogen as a protective gas.

[0057] (6) Add 0.2 mol of pyromellitic dianhydride to the reaction vessel and react for 12 h to obtain a viscous polyamic acid solution.

[0058] (7) The polyamic acid solution was uniformly coated on a 2×2cm glass plate, and then imidized at 200℃ for 1h in a heating furnace to obtain a PI composite film.

[0059] (8) Place the PI film into an isostatic graphite block and send it into a high-temperature graphitization furnace.

[0060] (9) First carbonize at 1100℃ for 1h in a high-temperature graphitization furnace, then graphitize at 2600℃ for 1h to obtain a graphene thermal conductive film.

[0061] Example 5: Preparation of the nickel-catalyzed graphene thermally conductive film of the present invention.

[0062] Includes the following steps: (1) Dissolve graphene powder and 0.2 mol of 4,4'-diaminodiphenyl ether in 1 L of DMAC and transfer it to a high-pressure reactor, using nitrogen as a protective gas.

[0063] (2) Add 0.2 mol of pyromellitic dianhydride to the reaction vessel and react for 8 h to obtain a viscous polyamic acid solution.

[0064] (3) The polyamic acid solution was uniformly coated on a 2×2cm glass plate, and then imidized at 200℃ for 1h in a heating furnace to obtain a PI composite film.

[0065] (4) Place the PI film into an isostatic graphite block and send it into a high-temperature graphitization furnace.

[0066] (5) First carbonize at 1200℃ for 1h in a high-temperature graphitization furnace, then graphitize at 3000℃ for 1h to obtain a graphene thermal conductive film.

[0067] As can be seen from the examples, the present invention can load nickel nanoparticles onto graphene and uniformly disperse graphene and nickel in a PI film, thereby effectively inducing and catalyzing the graphitization of polyimide during graphitization, reducing the graphitization temperature, improving the graphitization crystalline structure, and achieving the production of graphene thermal conductive films with lower energy consumption and better structure.

[0068] The graphitization temperature and thermal conductivity of the graphene thermally conductive films prepared in each embodiment are shown in Table 1 below: Graphitization temperature (°C) 1500 2400 2000 2600 3000 <![CDATA[Thermal conductivity W / (m -1 ·k -1 )]]> 2375 2079 2146 2052 1823 After multiple experimental adjustments, the nickel nanoparticles in Example 1 were more numerous, with particle sizes ranging from 40 to 60 nm and uniformly distributed within the graphene. Therefore, they had the most significant catalytic effect on graphitization, resulting in a low graphitization temperature and a well-structured graphene thermal conductive film with fewer amorphous defects, thus exhibiting excellent thermal conductivity. In Example 2, due to insufficient reducing agent and low pH value, the degree of reduction was low, the number of nickel nanoparticles was small and the particle size was uneven, so the catalytic effect was not obvious and the reduction of graphitization temperature was small. At the same time, the nickel nanoparticles were unevenly distributed in the graphite, so although the crystal structure of the graphene thermal conductive film was improved, there were still many amorphous defects, which limited the improvement of thermal conductivity. In Example 3, the reducing agent was sufficient, but the reaction time was too long, which caused the nickel nanoparticles to continue to grow after they were generated, resulting in agglomeration and the appearance of many large-diameter nickel nanoparticles. Although this catalyzed graphitization, the graphene thermal conductive film produced in the end still had certain amorphous defects in its crystalline structure due to the uneven size and distribution of the nickel nanoparticles. In Example 4, the nickel nanoparticles obtained by sodium borohydride reduction had poor dispersibility and were prone to agglomeration, resulting in large-particle-size nickel nanoparticles. At the same time, boron impurities were introduced, which hindered the catalytic effect of nickel. Therefore, the catalytic effect on graphitization was not as good as that of nickel nanoparticles reduced by hydrazine hydrate. Example 5 is a graphene thermal conductive film without added nickel nanoparticles. The addition of graphene improves the thermal conductivity of the graphene thermal conductive film, but the graphitization temperature requirement is still relatively high, resulting in high energy consumption.

Claims

1. A method for preparing a graphene thermally conductive film, characterized in that, Includes the following steps: a) Disperse 1g of nickel chloride hexahydrate in 200mL of aqueous solution and sonicate to obtain solution A; disperse 8g of graphene and 17mL of hydrazine hydrate in 800mL of aqueous solution, adjust the pH to 12 with 1mol / L sodium hydroxide solution, and sonicate to obtain solution B. b. Transfer solutions A and B to a high-pressure reactor and add 8g of N-methylpyrrolidone. React hydrothermally at 70°C for 7 hours. After cooling, centrifugation, washing, and drying, nickel-loaded graphene powder is obtained. c. Dissolve nickel-loaded graphene powder and diamine in N,N-dimethylacetamide (DMAC) and transfer to a high-pressure reactor. Use nitrogen as a protective gas, add dianhydride to the reactor, and react for 8 hours to obtain a viscous polyamic acid solution. d. The viscous polyamic acid solution is uniformly coated on a 2×2cm glass plate, and then imidized at 200℃ for 1h in a heating furnace to obtain a polyimide composite film. The film is placed in an isostatically pressed graphite block and sent to a high-temperature graphitization furnace. In the high-temperature graphitization furnace, it is first carbonized at 800℃ for 1h and then graphitized at 1500℃ for 1h to obtain a graphene thermal conductive film.

2. The method for preparing the graphene thermally conductive film according to claim 1, characterized in that: The diamine in step c is at least one of 4,4'-diaminodiphenyl ether, p-phenylenediamine, or poly(p-phenylene terephthalamide).

3. The method for preparing the graphene thermally conductive film according to claim 1, characterized in that: The dianhydride mentioned in step c is at least one of pyromellitic dianhydride, 4,4'-biphenyl ether dianhydride, or 1,2,4,5-benzenetetracarboxylic anhydride.

4. The method for preparing the graphene thermally conductive film according to claim 1, characterized in that: In step c, the mass ratio of nickel-loaded graphene powder to diamine is 1:1 to 10; the molar ratio of diamine to dianhydride is 1:

1.

5. The graphene thermal conductive film prepared by the method according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Graphene-loaded nickel magnetic composite material preparation method

    CN109107528A

  • Graphene induced polyimide oriented crystallization based high-thermal-conductivity graphite film preparation method

    CN110304625A